A Macro Model of the Credit Channel in a Currency Union Member : The Case of Benin - Samake, Issouf (IMF Working Papers; Working Paper, 2010)
This paper applies and extends a theoretical model built by Agenor and Montiel (2007) by exploring the effectiveness of government bonds and monetary policy in a small, open, credit-based economy with a fixed exchange rate. The model is applied to Benin, a member of a currency union, using a general equilibrium model with stochastic simulation. Model calibration replicates the historical pattern for 1996-2009. Policy experiments simulated an increase in government securities in Benin's regional market and a cut in the reserve requirement. Simulations produced mixed results. It appears that, among other factors, excess bank liquidity lowers the effectiveness of monetary policy instruments through the credit channel and that government bonds can help mop up excess bank liquidity.